Análise de corrosão em armaduras de concreto armado através de ensaio não destrutivo eletromagnético - Diógenes, Aldecira Gadelha (2021)
Reinforced concrete structures are susceptible to the appearance of corrosion in their reinforcement. Therefore, in order to obtain reliable and accurate information about the physical conditions of these reinforcements, as they play an important role in the stability of concrete structures, periodic inspections are required preferably non-destructive. Therefore, the present study proposes a non-destructive test, based on the electromagnetic induction technique, capable of discriminating the diameters of the steel rebars and identifying the presence of corrosion in them. This technique was simulated in the COMSOL Multiphysics program and performed in the laboratory. To simulate the corrosion in the reinforcements, the salt spray test was used. By means of signals obtained from sine or triangular waveform excitation magnetic field, hysteresis cycles were determined on rebar diameters of 5, 6.3, 8, 10, 12.5 and 16 mm, at depths of 0, 10 and 20 mm and with and without corrosion. From the hysteresis cycles, the maximum values of the fields, the remnant and the coercivity were obtained and analyzed by the mean and standard deviation and, they have also been organized in classes and classified by the pattern recognition techniques Principal Component Analysis, transform Karhunen-Loéve, Gaussian classifier and Artificial Neural Network implemented in the MATLAB program. The results showed that the proposed method can distinguish different diameters of reinforcement and has potential in the qualitative analysis of corrosion, although limited to a maximum depth.